Cyclophosphamide use in treatment of refractory Kawasaki disease with coronary artery aneurysms - Olha Halyabar; Kevin G. Friedman; Robert P. Sundel; Annette L. Baker; Margaret H. Chang; Patrick W. Gould; Jane W. Newburger; Mary Beth F. Son (BMC, 2021)
Abstract Background Despite timely administration of IVIG, some patients with Kawasaki disease (KD) develop rapidly progressive or giant coronary artery aneurysms (CAA). Case presentation We describe our experience using cyclophosphamide (CYC) for the treatment of such cases as well as a review of the literature on the use of CYC in KD. Through a retrospective chart review of our KD population, we identified ten children treated for KD with intravenous CYC (10 mg/kg/dose) for one or two doses. Seven patients were male, the median age was 2.0 years (range 4 months − 5 years). All patients received initial IVIG between day 4-10 of illness. Other anti-inflammatory treatments administered before CYC included second IVIG (n = 9), corticosteroids (n = 10), infliximab (n = 4), cyclosporine (n = 2), and anakinra (n = 1). Median illness day at administration of the first CYC dose was 22.5 days (range:10-36 days). The primary indication for treatment with CYC for all patients was large or giant CAA and/or rapid progression of CAA. Three patients received a second dose of CYC (10 mg/kg) for progressively enlarging CAA. CAA did not progress after final CYC treatment. One patient with a history of neutropenia in infancy developed severe neutropenia 9 days after treatment with CYC, which recovered without intervention or complications. No patient developed infections or other serious toxicity from CYC. Conclusion In KD patients with severe and progressive enlargement of CAA despite anti-inflammatory therapy, CYC seemed to arrest further dilation and was well-tolerated. Future multicenter studies are needed to confirm our findings in this subgroup of KD patients.